DSPACE implementation for a proportional–integral-based root mean square voltage controller used in stand-alone wind energy conversion systems. Issue 4 (August 2019) - El Akhrif, Rachid; Abbou, Ahmed; Laoufi, Chaymae; Ferfra, Mohamed
The induction machine and the synchronous machine are very promising in renewable energy production for uses in wind turbines to produce energy in remote areas, and we note that self-excited induction generator is more adapted due to difficult geographical conditions and best cost; on the other hand, permanent magnet synchronous generator works without any excitation system; all of these have a major problem in use which is the stability of voltage. To solve this problem, we propose in this article the examination of a control plot for keeping the produced root mean square voltage steady. This article presents an experimental comparative study of performances in terms of root mean square voltage on two possible small wind turbine systems. One of the systems is based on permanent magnet synchronous generator and the other is based on self-excited induction generator. Taking into account the parameters of load and wind speed, experimental test benches for both systems are implemented using the dSPACE card for controlling the pulse width modulation inverter to impose the Vrms value of the desired output voltage.